Effect of Different Egg Yolk Levels in Tris Extender With and Without Aloe Vera and Onion Crude Extracts on Surti Buck Semen at Refrigerated Temperature - Patel, Dignesh K.; Chaudhari, Chandrakant F.; Modi, Lalit C.; Chaudhari, Naresh F.; Chaudhary, Mahesh M.; Tyagi, Kuldeep K.; Kunvar, Sunil V. (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
This study aimed to develop a suitable Tris-citrate-fructose-egg yolk (Tris) based extender with Aloe vera or onion extract to preserve  Surti buck semen at refrigerated temperature. Semen ejaculates (n=96) collected by artificial vagina from eight bucks were split-diluted  in Tris extender with 0, 5, 10, 20% egg yolk concentrations. All these were then fractionated into three aliquiots each, one fracrtion kept  without further additives (EY0, EY5, EY10, EY20), while fractions 2 and 3 were an addition with crude filtrates of Aloe vera gel @ 10 µL  (EY0+A, EY5+A, EY10+A, EY20+A) or onion extract @ 10 µL (EY0+O, EY5+O, EY10+O, EY20+O) per 0.5 ml of the extended semen. These  samples (4x3 = 12 aliquots, each 0.5 ml) were then preserved at refrigerated temperature and evaluated at 12 hourly interval up to 48  h of storage for various sperm quality tests. Sperm motility was significantly lower (p
Keywords: Aloe vera; Egg yolk; Onion; Semen quality; Surti buck